PERSEPSI GURU TENTANG PARTISIPASI ORANGTUA SISWA DALAM PENYELENGGARAAN PENDIDIKAN DI SD N PUSAT KECAMATAN SIBERUT SELATAN KABUPATEN KEPULAUAN MENTAWAI - Lidiawati Samekmek (Jurnal Bahana Manajemen Pendidikan, 2014)
This study phenomena in the background show the parent participation to management of education. This study is intendedtoobtaininformationaboutan employee's perception learn about student parent participation in the form of materil, and non materil to management of education in SDN Center District Of South Siberut , Mentawai. The population is 52 teacher. The instrument usedin this studyis a questionnaire. In general, an employee's perception of the teacher about student parent participation to management of educationin the categoryquitewellwiththe overall averagescorewas3,1 Key Word: Parent Participation